Embracing the conceptual shift on new ways of experiencing the city and learning urban design: pedagogical methods and digital technologies. Issue 5 (2nd September 2016) - Mapua Lim, Regina; Novo de Azevedo, Laura; Cooper, Jon
Abstract: The innovations of the twenty-first century in digital technology and media have had major influences in the way young urbanites and future city designers think as well as experience places. In embracing this conceptual shift of how new communication technologies are changing people's perceptions, experiences and ways of knowing the city, Oxford Brookes University continues to develop pedagogical methods which use new media in the teaching, learning and production of contemporary urban design. These methods are examined in this paper in the context of three undergraduate modules: Taking the urban design learning experience out of the classroom and into the field using mobile lectures; Using digital media in research and engaging with oral, visual and sensory experiences; Developing design communication skills using video, animation, interactive PDFs and website design; Bringing new perspectives to classic theoretical concepts by engaging with different media: Cullen's Townscape from serial experiences in drawing to animated photographs and videos. These pedagogical innovations in experiencing, researching, designing and analyzing cityscapes have had a dramatic effect on the ability of students to transform themselves into design-aware and creative emerging practitioners. These are assessed for understanding the way students learn and the relevance of these skills for future practice.